Super hydrophobic SiO₂/phenolic resin-coated filter screen and its application in efficient oil–water separation - Zhao, Yan (2023)
The discharge of industrial liquid waste continues to cause more and more environmental problems. The current research aims at developing a durable and highly efficient filter screen for oil-water separation. In this paper, hydrophobic nano-SiO2 and phenolic resin were used as raw materials. Hydrophobic SiO2 particles were fixed on the surface of the coated filter screen by heating and curing the anchored particles. The surface morphology, element composition, surface roughness and water contact angle of the prepared super hydrophobic SiO2/phenolic resin-coated filter screen were analyzed and discussed by using SEM, EDS, AFM, OCA and other instruments. The results showed that the prepared filter screen contained Si, O, C elements, which proved that the resin coating film had adhered to the filter screen surface. When the aperture of the phenolic resin-coated filter screen was 400 meshes, the drainage angle reached a maximum value of 153.8° ± 0.8°. When two layers of hydrophobic SiO2 phenolic resin were coated on the screen, the surface of the filter screen had a sufficient nano-porous structure and high roughness. The tests showed that the minimum water contact angle of the filter screen exceeded 150°, which indicated excellent chemical resistance. Through the analysis of oil-water separation efficiency of isooctane, gasoline, n-hexane, dodecane, edible oil, dichloromethane and trichloromethane, it was concluded that the lowest separation efficiency for edible oil was 97.2%, and the highest separation efficiency for n-hexane was 99.4%. After 50 cycles of separation, the oil-water separation efficiency for n-hexane was still at 99%.